2021
DOI: 10.3748/wjg.v27.i20.2643
|View full text |Cite
|
Sign up to set email alerts
|

Association between oral contraceptive use and pancreatic cancer risk: A systematic review and meta-analysis

Abstract: BACKGROUND Studies on the association of oral contraceptive (OC) use and pancreatic cancer showed inconsistent findings. AIM To evaluate the relationship between OC use and pancreatic cancer risk. METHODS A literature search for observational studies (case-control and cohort studies) was conducted up to December 2020. A meta-analysis was performed by calculating pooled relative risks (RRs) and 95% confidence intervals (CIs). Heterogeneity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(50 reference statements)
0
3
1
Order By: Relevance
“…Based on the results of the recalculated sRRs and DRMA, the OCU may not be associated with the risk of PCW. Because my conclusion contradicts that reported by Ilic et al [ 1 ], it is necessary to re-evaluate the direction and statistical significance of risk through an updated meta-analysis in the future.…”
Section: To the Editorcontrasting
confidence: 65%
See 2 more Smart Citations
“…Based on the results of the recalculated sRRs and DRMA, the OCU may not be associated with the risk of PCW. Because my conclusion contradicts that reported by Ilic et al [ 1 ], it is necessary to re-evaluate the direction and statistical significance of risk through an updated meta-analysis in the future.…”
Section: To the Editorcontrasting
confidence: 65%
“…I recently read the systematic review and meta-analysis conducted by Ilic et al [ 1 ] comprising 10 case-control studies and 11 cohort studies, which concluded that the use of oral contraceptives (OCU) was associated with a decreased risk of pancreatic cancer in women (PCW) [summary relative risk (sRR) = 0.85; 95% confidence intervals (CI) = 0.73-0.98; P = 0.03]. Interestingly, the subgroup analysis according to the study design showed no statistical significance in case-control studies but showed borderline statistical significance in cohort studies (sRR = 0.84; 95%CI = 0.70-1.00; P = 0.05).…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…HRT has, in fact, been observed to reduce the risk of pancreatic cancer 73 . OCP use, on the other hand, might reduce risk in postmenopausal women but the results at this point are unclear 74 . Another drawback of the current study lies with the lack of or insufficient information on grading, staging, tumour size, and diabetes type, but cohorts with samples taken years before diagnosis are scarce.…”
Section: Discussionmentioning
confidence: 99%